POLA HIDUP TIDAK TERATUR DAN AKTIVITAS FISIK BERLEBIH MENURUNKAN KEMAMPUAN AKTIVITAS SEKSUAL - Pangkahila, Erwin Adams; Milas Siswanto, Ferbian (Sport and Fitness Journal; Volume 3, No.1, 2015, 2015)
One important aspect that determines the quality of human life is sexual life. Therefore,  sexual activity to be one part in the assessment of the quality of human life. In everyday life, not infrequently encountered sexual problem in various communities, an estimated 322 million people both men and women experience sexual dysfunction worldwide. One of the factors that cause sexual dysfunction that is very important is lifestyle. Lifestyle that includes physical activity would interfere with organ function so that the body is not healthy and does not fit include decreased sexual fitness. Many studies have reported that the results of unhealthy lifestyle, especially diet and sleep patterns, can interfere with a person's sexual ability. In addition to lifestyle, excessive physical activity also decreases sexual function. But in contrast, a good control on lifestyle and physical activity will enhance the ability of sexual activity.
Keywords: lifestyle, physical activity, sexual function